Hydrogen-bonded silicene nanosheets of engineered bandgap and selective degradability for photodynamic therapy. (November 2021) - Xu, Deliang; Lin, Han; Qiu, Wujie; Ge, Min; Chen, Zhixin; Wu, Chenyao; You, Yanling; Lu, Xiangyu; Wei, Chenyang; Liu, Jianjun; Guo, Xiang; Shi, Jianlin
Abstract: Silicon, a highly biocompatible and ubiquitous chemical element in living systems, exhibits great potentials in biomedical applications. However, the silicon-based nanomaterials such as silica and porous silicon have been largely limited to only serving as carriers for delivery systems, due to the lack of intrinsic functionalities of silicon. This work presents the facile construction of a two-dimensional (2D) hydrogen-bonded silicene (H-silicene) nanosystem which is highlighted with tunable bandgap and selective degradability for tumor-specific photodynamic therapy facilely by surface covalent modification of hydrogen atoms. Briefly, the H-silicene nanosheet material is selectively degradable in normal neutral tissues but rather stable in the mildly acidic tumor microenvironment (TME) for achieving efficient photodynamic therapy (PDT). Such a 2D hydrogen-bonded silicene nanosystem featuring the tunable bandgap and tumor-selective degradability provides a new paradigm for the application of multi-functional two-dimensional silicon-based biomaterials towards the diagnosis and treatments of cancer and other diseases. Graphical abstract: Due to the zero-bandgap characteristic of silicene nanosheets, this work construct a two-dimensional (2D) hydrogen-bonded silicene (H-silicene) nanosystem with tunable bandgap by surface covalent modification of hydrogen atoms. The H-silicene nanosheet could achieve efficient photodynamic therapy (PDT) by the ROS production based on its semiconducting character. Moreover, the H-silicene is are rather stable in the weakly acidic tumor microenvironment in comparison with the quick degradation in the neutral bio-milieu of normal cells and tissues. Image 1